Penerapan Undang Undang Otonomi Daerah No. 32 Tahun 2004 Jo Perda No. 7 Tahun 2006 di Waru Sidoarjo - Azmi M., Ulul (Prodi Siyasah Jinayah (Hukum Tata Negara dan Hukum Pidana Islam) Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2013)
Abstract: This article is a field research on the application of the Regional Autonomy Law No. 32 year 2004, jo PERDA (Regional Regulation) No. 7 year 2006 about the local government in Waru-Sidoarjo. The research was conducted by interviewing some people from four villages, namely Ngingas, Kepuh Kiriman, Tambak Oso, and Tambak Rejo. The research concludes that the community of the four villages had been carrying out the mandate of the Regional Autonomy Law No. 32 year 2004, jo PERDA (Regional Regulation) No. 7 year 2006. However, the compliance in carrying out the law is not based on their legal awareness. It is because there are some laws that are considered as discrimination and murder of the rights of individuals, including the prohibition of the village government to take charge of the political party (consulting / comparative study)